Isolation and Characterization Secondary Metabolites ÃâÃâSemi-PolarÃâÃâ Fraction of Sembung Plants (Blumea balsamifera) - MUJAHID MUSLIM ( NIM : 10509091 ), SYAHID
Indonesia has a very large biodiversity which has largely been widely used as a medicinal plant. Sembung plants (Blumea balsamifera) is a species of plant in the family Asteraceae which has been used as a medicinal plant in various countries , such as China, Thailand, Philippines and Indonesia. Sembung used to treat diseases such as flatulence (carminati), rheumatism, diarrhea, cleans 'blood' for new mothers, diuretic, until to treat diabetic. Various studies have been reported, from the content of secondary metabolites to the bioactivity of Sembung (B. balsamifera) plant such as anti-tyrosinase, anti-cancer, plasmin-inhibitor, NO-inhibitors and antitumor. However, until now, just a few studies secondary metabolites content of Sembung (B. balsamifera) plant from Indonesia. Therefore, research is done to isolate the secondary metabolites of Sembung (B. balsamifera) plants from Indonesia. Isolation is done by extraction using methanol and then fractionated by Vacuum Liquid Chromatography and Radial Chromatography techniques. Two compounds have been isolated from the aerial parts (twigs, leaves, and flowers) Sembung plants (B. balsamifera) that eluted in 'semi-polar' fractions. This compound is identified as a derivative of the flavonoids named sterubin and sesquiterpene guaian named blumeane-E1. Structure elucidation based on data that include UV-Vis spectroscopy, 1D NMR(1H, 13C and TOCSY) and 2D NMR (DEPT-135, HMQC, HSQC, HMBC, and NOESY).